Moran Brothers employees working at lumber yard, Seattle, circa 1900
After working on ships for a number of years Robert Moran (1857-1943) opened a marine repair shop at Yesler's Wharf in 1882. Shortly thereafter he established Moran Brothers Marine and Sawmill Machinery Company (later Moran Brothers Company) with his brothers, Frank Moran (1860-1934) and Sherman Moran (1865-1929). The firm built steamers and barges for miners on the Yukon River, as well as many large steel and wood vessels, including the battleship USS Nebraska for the U. S. Navy. This image of the Moran Brothers lumber yard, located at the foot of South Charles Street south of Pioneer Square, was taken between 1894-1906. Several employees can be seen at work, highlighting the busy pace at the yard. 1 photographic print mounted on cardboard; b&w; 7.75 x 9.75 in.